A documentary history of Jewish-Christian relations: from antiquity to the present day - Kessler, Edward; Wenborn, Neil (Cambridge University Press, 2024)
Jews and Christians have interacted for two millennia, yet there is no comprehensive, global study of their shared history. This book offers a chronological and thematic approach to that 2,000-year history, based on some 200 primary documents chosen for their centrality to the encounter. A systematic and authoritative work on the relationship between the two religions, it reflects both the often troubled history of that relationship and the massive changes of attitude and approach in more recent centuries. Written by a team leading international scholars in the field, each chapter introduces the context for its historical period, draws out the key themes arising from the relevant documents, and provides a detailed commentary on each document to shed light on its significance in the history of the Jewish-Christian relationship. The volume is aimed at scholars, teachers and students, clerics and lay people, and anyone interested in the history of religion.